Desarrollo De Un Dispositivo Para El Primer Acercamiento Al Atletismo Paralímpico Que Permita Optimizar La Comunicación Y Sincronización Entre El Guía Y Atleta. (2024)
Athletics in its different characteristics incorporates fundamental skills for its athletes such as coordination, concentration and physical capacity for better performance, therefore, can offer benefits to different people to improve their living condition as is the case of people with visual limitations. This population has special attention due to its condition, since they have few activities that allows them to adapt to their reality, which can affect their well-being emotional, generating social interaction problems.